Assessment and improvement of energy utilization in palm oil mill by using Microsoft Excel and Aspen HYSYS software: article - Ahya, Muhammad Khairil; Abu Bakar, Noor Fitrah (2019)
Despite having a significant contribution to the economic growth, palm oil mill industry is undoubtedly categorized as a sector that consumes enormous energy. However, the energy consumed or utilized in the palm oil mill need to be managed properly in order to minimize the excess of energy generated. In this study, an actual crude palm oil process located at Bestari Jaya, Malaysia was analyzed using energy assessment approached and process simulation. This was intended to assess the amount of energy required in the palm oil mill as well as to define possibilities in improving the energy utilization in the palm oil mill. The energy assessment was conducted by performing mass and energy balance analysis by using Microsoft Excel, while goal seek method in the Microsoft Excel and process simulation by using Aspen HYSYS V8.8 were also conducted to predict the theoretical amount of steam and energy required for the crude palm oil process. Based on the assessment conducted, the amount of steam consumed in the sterilization and digestion process were obtained at 0.13 ton/h FFB and 0.04 ton/h FFB respectively. These values were considered acceptable since both values shows a good agreement with other studies. Besides, the total actual amount of steam and energy utilization was also obtained through the assessment; the values were 15283 kg/h of steam and 10980 kW respectively. But, through goal seek method and process simulation, the result indicates that the reduction of energy and steam utilization in the selected palm oil mill can be made up to 9.51% and 10.41% respectively. As a conclusion, it is proposed that better control system should be employed in the palm oil mill such as implementing a proper control system for temperature and flowrate as to monitor the steam utilization. Besides, proper maintenance of equipments was also suggested to be conducted in the plant as to improve the efficiency of equipments, so that, heat loss generation could also be minimized.